The Difference in the Cyclin D1 Expression in Advanced Stage Nasopharyngeal Cancer based on Treatment Response: A Retrospective Cohort Study - Cosphiadi Irawan; Rahmat Cahyanur; Lisnawati Lisnawati; Murdani Abdullah; Reyhan Eddy Yunus (Interna Publishing, 2020)
Background: nasopharyngeal cancer (NPC) is the most common type of head and neck cancer in Indonesia (28.4%). Reports showed that 18.9% of cases came with advanced stage. Chemotherapy play important role in advanced stage. However, patients with the same stage of the disease may have different treatment response, likely due to the different tumor biological characteristics. Cyclin D1 is a protein involved in the cell cycle, which will stimulate proliferation. This study aimed to examine the proportion of cyclin D1 in NPC and its association with treatment response. Methods: a retrospective cohort study was conducted on advanced NPC patients that underwent chemotherapy at Cipto Mangunkusumo Hospital from 2015 until 2018. Cyclin D1 immunohistochemistry staining was done by antigen retrieval methods using the cyclin D1 NovocastraTM monoclonal antibody. The cyclin D1 expression was evaluated with h-score. Treatment response was reviewed based on the RECIST 1.1 criteria. Results: fifteen subjects (48.4%) had a positive expression of cyclin D1. Higher proportion of cyclin D1 positive was found in responsive group compare with non-responsive group (66.7% vs. 33.3%, p = 0.032). Statistically significant difference in mean h-score was observed between the subjects who responded and those who did not respond (116.24 SD57.80 vs. 77.97 SD45.27, p = 0.048). Conclusion: this study suggests that a higher expression of cyclin D1 is associated with a good treatment response in NPC patients.